2019
DOI: 10.21873/invivo.11507
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Mid-to-Long-term Outcomes Following Ankle Arthrolysis

Abstract: Background: The aim of this study was to evaluate the clinical and radiographic success of arthrolysis surgery and the risk of progression of osteoarthrosis at the ankle joint. Materials and Methods: In a retrospective clinical and radiological study, with a minimum follow-up of 24 months, the pain level and quality of living were evaluated. Results: Following arthrolysis of the ankle joint, 16% of patients required ankle fusion within 2 years. Women had a higher quality-of-life in terms of Foot Function Index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Lower AOFAS scores confirm poor functional performance in daily activities, quality-of-life, and movement (38). Whereas Rohlfing et al could not find any correlation between BMI and AOFAS or VAS in their 66.9 (range=4-186) months follow-up study of 51 patients with ankle arthrolysis (39). Future studies should examine these effects in greater cohorts and to provide more detailed analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Lower AOFAS scores confirm poor functional performance in daily activities, quality-of-life, and movement (38). Whereas Rohlfing et al could not find any correlation between BMI and AOFAS or VAS in their 66.9 (range=4-186) months follow-up study of 51 patients with ankle arthrolysis (39). Future studies should examine these effects in greater cohorts and to provide more detailed analysis.…”
Section: Discussionmentioning
confidence: 95%
“…The ankle arthrodesis or fusion has represented, in the past and still now in determined cases, the surgical gold standard for the ankle end-stage osteoarthritis [15,16]. After an ankle arthrodesis, even at 20 years of follow-up, about 90% of satisfaction was reported, but at the same time some studies have shown that in the years following the surgery, the patient may develop a degenerative arthropathy of the adjacent homolateral joints [17][18][19][20]. In recent years, the total ankle replacement has gained considerable popularity but, unlike the knee and hip prosthesis, it is relatively "young".…”
Section: Discussionmentioning
confidence: 99%
“…Die arthroskopische Arthrolyse wird für die Behandlung einer Bewegungseinschränkung sowohl am Schultergelenk ("frozen shoulder" [11]) als auch am Kniegelenk bei Arthrofibrose [12] und am Sprunggelenk (arthrotisch induzierte Bewegungseinschränkung [13]…”
Section: Arthroskopische Arthrolyseunclassified